High-brightness EUV source based on laser plasma using a liquid-metal droplet target. (May 2016) - Vinokhodov, A.Yu.; Krivokorytov, M.S.; Sidelnikov, Yu.V.; Krivtsun, V.M.; Medvedev, V.V.; Koshelev, K.N.
Abstract: We present the study of a source of extreme ultraviolet (EUV) radiation based on laser plasma generated due to the interaction of radiation from a nanosecond Nd : YAG laser with a liquid-metal droplet target consisting of a low-temperature eutectic indium – tin alloy. The generator of droplets is constructed using a commercial nozzle and operates on the principle of forced capillary jet decomposition. Long-term spatial stability of the centre-of-mass position of the droplet with the root-mean-square deviation of is demonstrated. The use of a low-temperature working substance instead of pure tin increases the reliability and lifetime of the droplet generator. For the time- and space-averaged power density of laser radiation on the droplet target and the diameter of radiating plasma, the mean efficiency of conversion of laser energy into the energy of EUV radiation at equal to 2.3 % is achieved. Using the double-pulse method, we have modelled the repetitively pulsed regime of the source operation and demonstrated the possibility of its stable functioning with the repetition rate up to for the droplet generation repetition rate of more than, which will allow the source brightness to be as large as .